Effectiveness and implementation analysis of interventions to improve exclusive and early initiation of breastfeeding in West Africa - Salm, Leah; Touré, Mariama; Diatta, Dieynab; Campbell, Fiona; Booth, Andrew; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
Transform Nutrition West Africa has identified key priorities for future action in the West Africa region. It has done so in consultation with stakeholders, including researchers, NGOs, members of civil society and the private sector, and representatives from government, the United Nations, and donor agencies. Consultations involved capturing, documenting, and learning from implementation experiences, and accelerating equitable program coverage of mother, infant, and young child interventions at scale. Stakeholders specifically identified the need for contextualization and implementation of interventions to promote breastfeeding.